A mechanistic model of SAG mills - Rodrigo Carvalho; Marcelo Tavares (International Mineral Processing Congress, 2014)
"The accurate prediction of the outcomes in SAG grinding has been a great challenge to researchers and process operators. The use of Discrete Element Methods for modelling charge motion in tumbling mills allowed extraction of not only visual data, such as the position of the charge, but also the energy transfer in terms of the energy dissipated in the collisions. One of the advantages of DEM technique is its scalability to different mill sizes and some operational conditions such as speed and mill filling. Recently the Authors proposed the coupling between DEM outputs and modified Population Balance Models that with proper dedicated ore characterization tests allows the prediction of the outcomes of an energy transfer example. This modelling framework is called the Multi-scale Mechanistic Modelling. This paper shows the application of the Multi-scale Mechanistic Model to a set of pilot plant tests ran at different operational conditions. The prediction of the grinding outcomes and even the stabilization of the charge was achieved by the use of the Multi-scale Mechanistic Modelling framework. This approach has a great potential to become a powerful tool to design and optimize AG and SAG mills."